PVC recycled polyvinyl chloride plastic and preparation method thereof
Patent Information
- Application Number
- CN202610323789.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-17
- Publication Date
- 2026-06-26
AI Technical Summary
Existing recycled PVC materials suffer from insufficient interfacial bonding strength, performance degradation due to molecular chain breakage, and easy migration and loss of functional additives in high-strength applications, making it difficult to meet the long-term and high-performance requirements of composite materials.
A dynamic cross-linking network is formed in the recycled PVC matrix using a thermally reversible covalent cross-linking agent, and fibrous filler is generated in situ using a stretching rheological plasticizing device. Combined with a woven carbon fiber layer and a gradient interface layer, chemical bonding is used to form a reinforcing connection, thus constructing a 'dual-network reinforced' structure.
It significantly improves the tensile strength and flexural modulus of composite materials, solves the interlaminar delamination problem, and maintains the multifunctionality and stability of the material.
Smart Images

Figure CN122275398A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of PVC recycled plastics technology, specifically to a PVC recycled polyvinyl chloride plastic and its preparation method. Background Technology
[0002] Polyvinyl chloride (PVC), one of the five major general-purpose plastics, boasts advantages such as low price, corrosion resistance, and good flame retardancy, making it widely used in building pipes, wires and cables, packaging materials, and automotive parts. With the increasing consumption of plastic products year by year, the disposal of waste PVC plastic has become a serious environmental problem. Recycled PVC materials undergo thermo-oxidative aging and mechanical degradation during processing and use, resulting in broken molecular chains and a significant decline in mechanical properties, making it difficult to meet the demands of high-strength applications. To address this issue, existing technologies typically modify recycled PVC by adding reinforcing fibers, inorganic fillers, or blending it with other polymer materials. However, the above methods still have the following problems in practical use: First, the interfacial bonding strength is insufficient. The recycled PVC matrix and the reinforcing fiber layer are usually only physically bonded or simply bonded at the interface. Under long-term stress or thermal cycling conditions, interlayer delamination is very likely to occur, leading to the overall failure of the composite material. Secondly, the properties of recycled PVC matrix itself are deteriorated. The molecular weight of recycled PVC is reduced and the molecular weight distribution is widened. Simply relying on external fiber reinforcement cannot fundamentally solve the problems of insufficient matrix strength and poor thermal stability.
[0003] Third, the functions are limited and lack long-term effectiveness. Multiple functions are given to the material by adding a variety of functional additives (such as flame retardants, antistatic agents, thermally conductive fillers, etc.), but these additives lack synergistic effects and are easily migrated and lost during processing and use, resulting in functional degradation. Summary of the Invention
[0004] The purpose of this invention is to provide a recycled PVC plastic and its preparation method, which has the effect of improving mechanical properties and interfacial bonding strength.
[0005] The above-mentioned technical objective of the present invention is achieved through the following technical solution: a recycled PVC plastic, comprising a recycled PVC matrix phase, a gradient interface layer, and a braided carbon fiber reinforcement layer. The recycled PVC matrix phase contains a thermally reversible covalent crosslinking agent comprising 1% to 5% of its mass. The thermally reversible covalent crosslinking agent forms a dynamic crosslinking network within the recycled PVC matrix phase. The braided carbon fiber reinforcement layer is disposed on the outer surface of the recycled PVC matrix phase, and the carbon fibers constituting the braided carbon fiber reinforcement layer have active functional groups grafted onto their surfaces, capable of chemically reacting with the thermally reversible covalent crosslinking agent. The gradient interface layer is located between the recycled PVC matrix phase and the braided carbon fiber reinforcement layer, and is formed by the thermally reversible covalent crosslinking agent in the recycled PVC matrix phase penetrating and diffusing into the braided carbon fiber reinforcement layer, and chemically bonding with the active functional groups on the carbon fiber surface. The component concentration of the gradient interface layer exhibits a continuous gradient change in the thickness direction.
[0006] A further feature of the present invention is that the thermally reversible covalent crosslinking agent is a furfuryl maleimide modified compound containing a Diels-Alder structure, and the active functional groups grafted onto the carbon fiber surface are epoxy groups or carboxyl groups.
[0007] A further feature of the present invention is that graphene quantum dots and rare earth complexes are dispersed in the gradient interface layer, wherein the particle size of the graphene quantum dots is 2-10 nm, and the rare earth complexes are cerium complexes or lanthanum complexes.
[0008] A further feature of the present invention is that the recycled PVC matrix phase is further dispersed with in-situ generated fibrous inorganic filler, the aspect ratio of which is 10:1 to 50:1, and is formed by in-situ stretching of particulate filler with a particle size of 50-200 nm under the action of a stretching flow field.
[0009] A further provision of the present invention is that the in-situ generated fibrous inorganic filler is at least one of fibrous calcium oxide-basic iron oxide-titanium dioxide composite filler, fibrous cryolite, or fibrous ceramic micropowder.
[0010] A method for preparing recycled PVC plastic, characterized by comprising the following steps: S1: Raw material pretreatment: Recycled PVC resin, thermally reversible covalent crosslinking agent, filler and additives are mixed to obtain a mixture. The braided carbon fiber layer is immersed in a modified liquid containing active functional groups. After being taken out, it is subjected to semi-curing treatment to obtain a pretreated braided carbon fiber layer with active functional groups grafted on the surface. S2: In-situ fiber formation plasticization: The mixture obtained in step S1 is added to the stretching rheological plasticizing extrusion equipment and plasticized and mixed under the action of the stretching flow field, so that the filler in the mixture is stretched in-situ to form a fibrous structure under the action of the stretching flow field, and fiber-reinforced plasticized melt is obtained. S3: Integral molding and infiltration: The fiber-reinforced plasticized melt obtained in step S2 is injected into a mold. The mold contains a pre-treated braided carbon fiber layer obtained in step S1. Under the conditions of temperature 150-200℃ and pressure 10-30 MPa, the thermally reversible covalent crosslinking agent in the plasticized melt penetrates and diffuses into the interior of the pre-treated braided carbon fiber layer and chemically bonds with the active functional groups on the surface of the carbon fiber to form a gradient interface layer. S4: Cooling and molding: After holding the pressure and cooling, open the mold and take out the product to obtain recycled PVC plastic.
[0011] A further feature of the present invention is that the stretching rheological plasticizing extrusion equipment in step S2 is an eccentric rotor extruder or a blade extruder, and its stretching strain rate is 50 s⁻¹. -1 ~200 s -1 .
[0012] A further setting of the present invention is that the permeation and diffusion time in step S3 is 30-120 seconds, and the thickness of the gradient interface layer is 100-500 μm.
[0013] In summary, the present invention has the following beneficial effects: 1. A dynamic cross-linking network is formed inside the recycled PVC matrix by a thermally reversible covalent cross-linking agent, which effectively compensates for the strength loss caused by molecular chain breakage in recycled PVC. At the same time, the granular filler is fiberized in situ using a tensile rheological plasticizing device, forming a micro-fiber reinforcement network in the matrix. The macro-woven carbon fiber layer and the micro-in situ fiber-forming network constitute a "double network reinforcement" structure, which makes the tensile strength of the composite material reach more than 86 MPa and the flexural modulus reach more than 4.8 GPa, which is far superior to existing recycled PVC composite materials. 2. Through the penetration diffusion and chemical bonding of thermally reversible covalent crosslinking agents, a gradient interface layer with a component gradient change is constructed between the recycled PVC matrix and the woven carbon fiber layer. This interface layer is not a simple physical bonding, but connects the matrix and the reinforcing layer into a whole through chemical bonds (such as the reaction of DA bonds with epoxy groups), which fundamentally solves the industry problem of easy delamination of multilayer composite materials. Attached Figure Description
[0014] Figure 1 This is a cross-sectional structural diagram of the present invention.
[0015] In the diagram: 1. Recycled PVC matrix phase; 2. Gradient interface layer; 3. Braided carbon fiber reinforcement layer. Detailed Implementation
[0016] The present invention will be further described below with reference to the accompanying drawings in the embodiments of the present invention.
[0017] Example 1: This example provides a recycled PVC plastic, the structure of which is as follows: Figure 1 As shown, it includes a recycled PVC matrix phase 1, a woven carbon fiber reinforcement layer 3, and a gradient interface layer 2 located between the two.
[0018] The raw materials for preparing recycled PVC matrix phase 1 include, by weight, 100 parts recycled PVC resin, 3 parts thermally reversible covalent crosslinking agent, 12 parts filler, 5 parts plasticizer, 2 parts heat stabilizer, and 1 part antioxidant. The thermally reversible covalent crosslinking agent is a furfuryl maleimide modified compound (DA bond compound), which contains a Diels-Alder structure and can undergo a reversible ring-opening reaction at high temperatures. The filler is a calcium oxide-basic iron oxide-titanium dioxide composite particle (CaO·FeOOH·TiO2) with a particle size of 100 nm. The plasticizer is tributyl citrate. The heat stabilizer is di-n-octyltin maleate. The antioxidant is 4,4'-bis(2,2-dimethylbenzyldiphenylamine).
[0019] The woven carbon fiber reinforcement layer 3 uses 3K carbon fiber woven fabric, and the surface of the carbon fiber is pre-grafted with epoxy active functional groups. The specific treatment method is as follows: the carbon fiber woven fabric is immersed in a modified liquid containing epichlorohydrin, reacted at 60°C for 2 hours, and then semi-cured at 80°C for 30 minutes to obtain a pre-treated woven carbon fiber layer with surface-grafted epoxy groups.
[0020] The preparation method of the composite material in this embodiment is as follows: Raw material pretreatment: Add recycled PVC resin, thermally reversible covalent crosslinking agent, filler, plasticizer, heat stabilizer and antioxidant to a high-speed mixer according to the above ratio, and mix at 800 rpm for 15 minutes to obtain a mixture. In-situ fiber formation and plasticization: The mixture is fed into an eccentric rotor extruder (tensile strain rate of 100 s). -1 In the process, plasticizing and mixing are carried out at 180°C, so that the particulate fillers in the mixture are stretched in situ under the action of the stretching flow field to form a fibrous structure, thus obtaining a fiber-reinforced plasticized melt. Integrated molding and infiltration: The fiber-reinforced plasticized melt obtained above is injected into a mold, and the pretreated braided carbon fiber layer obtained above is placed in the mold beforehand; the pressure is maintained at 180°C and 20MPa for 60 seconds, so that the thermally reversible covalent crosslinking agent in the plasticized melt penetrates and diffuses into the interior of the pretreated braided carbon fiber layer and chemically bonds with the epoxy groups on the surface of the carbon fiber to form a gradient interface layer with a thickness of about 300μm. Cooling and molding: After the pressure holding is completed, the temperature is reduced to 40°C at a cooling rate of 10°C / min. The mold is then opened and the product is removed to obtain recycled PVC plastic.
[0021] Example 2: This example is basically the same as Example 1, except that: the thermally reversible covalent crosslinking agent is a furan-maleimide adduct with a Diels-Alder structure, and the amount is 2 parts; graphene quantum dots and cerium complex CeO2·Ce2O3 are also dispersed in the gradient interface layer 2, wherein the graphene quantum dots have a particle size of 5 nm and the amount of cerium complex is 10% of the mass of the thermally reversible covalent crosslinking agent; the graphene quantum dots and cerium complex are pre-dispersed in the pretreatment modification liquid of carbon fibers, and the above components are introduced at the same time as the epoxy groups are grafted on the surface of the carbon fibers, so that in the subsequent integral molding process, the graphene quantum dots and cerium complex diffuse into the gradient interface layer together with the thermally reversible covalent crosslinking agent.
[0022] In the preparation method, the stretch rheological plasticizing equipment uses a blade extruder with a stretch strain rate of 150 s⁻¹. -1 The one-piece molding permeation conditions are: temperature 170℃, pressure 25MPa, and holding time 90 seconds.
[0023] Example 3: This example is basically the same as Example 1, except that: the filler is Na3AlF6 cryolite particles with a particle size of 80nm, which are in situ formed into fibrous cryolite filler under the action of a tensile flow field, with an aspect ratio of 30:1; the amount of thermally reversible covalent crosslinking agent is 4 parts; lanthanum complex La2O3 is dispersed in the gradient interface layer; in the preparation method, the integral molding penetration time is 120 seconds, and the thickness of the gradient interface layer is about 450μm.
[0024] Example 4: This example provides a recycled PVC plastic with the same structure as Example 1, the difference being the fluctuation in raw material ratio and process parameters.
[0025] The raw materials for preparing recycled PVC matrix phase 1 include, by weight: 100 parts recycled PVC resin, 1 part thermally reversible covalent crosslinking agent (furyl maleimide modified compound), 8 parts filler (calcium oxide-basic iron oxide-titanium dioxide composite particles), 3 parts plasticizer, 1 part heat stabilizer, and 0.5 parts antioxidant.
[0026] In the preparation method, the stretch rheological plasticizing equipment uses an eccentric rotor extruder with a stretch strain rate of 50 s⁻¹. -1 The plasticizing temperature is 160℃; the integral molding penetration conditions are 150℃ temperature, 10MPa pressure, and 30 seconds holding time, forming a gradient interface layer with a thickness of about 100μm.
[0027] Example 5: This example is basically the same as Example 4, except that the raw material ratio of recycled PVC matrix phase 1 is as follows: 100 parts recycled PVC resin, 5 parts thermally reversible covalent crosslinking agent (furyl maleimide modified compound), 15 parts filler (calcium oxide-basic iron oxide-titanium dioxide composite particles), 8 parts plasticizer, 3 parts heat stabilizer, and 2 parts antioxidant; in the preparation method, the tensile strain rate is 200 s. -1 The plasticizing temperature is 200℃; the integral molding penetration conditions are 200℃ temperature, 30MPa pressure, and 120 seconds holding time, forming a gradient interface layer with a thickness of about 500μm.
[0028] Example 6: This example is basically the same as Example 1, except that the active functional group grafted onto the carbon fiber surface in the woven carbon fiber reinforcement layer 3 is a carboxyl group, rather than an epoxy group. The specific treatment method is as follows: the woven carbon fiber fabric is immersed in a modified solution containing maleic anhydride and reacted at 70°C for 3 hours to graft carboxyl groups onto the carbon fiber surface; the thermally reversible covalent crosslinking agent is a DA bond compound containing hydroxyl groups, which can undergo esterification with the carboxyl groups to form chemical bonds.
[0029] The above description is only a preferred embodiment of the present invention. Therefore, all equivalent changes or modifications made to the structure, features and principles described in the claims of this patent application are included in the scope of this patent application.
Claims
1. A recycled PVC plastic, comprising a recycled PVC matrix phase (1), a gradient interface layer (2), and a woven carbon fiber reinforcement layer (3), characterized in that, The recycled PVC matrix phase (1) contains a thermally reversible covalent crosslinking agent of 1% to 5% of its mass. The thermally reversible covalent crosslinking agent forms a dynamic crosslinking network inside the recycled PVC matrix phase. The braided carbon fiber reinforcement layer (3) is disposed on the outer surface of the recycled PVC matrix phase (1), and the carbon fiber surface constituting the braided carbon fiber reinforcement layer (3) is grafted with active functional groups that can chemically react with the thermally reversible covalent crosslinking agent. The gradient interface layer (2) is located between the recycled PVC matrix phase (1) and the braided carbon fiber reinforcement layer (3), and is formed by the thermally reversible covalent crosslinking agent in the recycled PVC matrix phase (1) penetrating and diffusing into the braided carbon fiber reinforcement layer (3) and chemically bonding with the active functional groups on the surface of the carbon fiber. The component concentration of the gradient interface layer (2) changes continuously in the thickness direction.
2. The recycled PVC plastic according to claim 1, characterized in that: The thermally reversible covalent crosslinking agent is a furfuryl maleimide modified compound containing a Diels-Alder structure, and the active functional groups grafted onto the carbon fiber surface are epoxy or carboxyl groups.
3. The recycled PVC plastic according to claim 1, characterized in that: The gradient interface layer (2) also contains graphene quantum dots and rare earth complexes, wherein the particle size of the graphene quantum dots is 2-10 nm, and the rare earth complexes are cerium complexes or lanthanum complexes.
4. The recycled PVC plastic according to claim 1, characterized in that: The recycled PVC matrix phase (1) also contains in-situ generated fibrous inorganic fillers, the aspect ratio of which is 10:1 to 50:1, and which are formed by in-situ stretching of granular fillers with a particle size of 50-200 nm under the action of a stretching flow field.
5. The recycled PVC plastic according to claim 4, characterized in that: The in-situ generated fibrous inorganic filler is at least one of fibrous calcium oxide-basic iron oxide-titanium dioxide composite filler, fibrous cryolite, or fibrous ceramic micropowder.
6. A method for preparing recycled PVC plastic, characterized in that, Includes the following steps: S1: Raw material pretreatment: Recycled PVC resin, thermally reversible covalent crosslinking agent, filler and additives are mixed to obtain a mixture. The braided carbon fiber layer is immersed in a modified liquid containing active functional groups. After being taken out, it is subjected to semi-curing treatment to obtain a pretreated braided carbon fiber layer with active functional groups grafted on the surface. S2: In-situ fiber formation plasticization: The mixture obtained in step S1 is added to the stretching rheological plasticizing extrusion equipment and plasticized and mixed under the action of the stretching flow field, so that the filler in the mixture is stretched in-situ to form a fibrous structure under the action of the stretching flow field, and fiber-reinforced plasticized melt is obtained. S3: Integral molding and infiltration: The fiber-reinforced plasticized melt obtained in step S2 is injected into a mold. The mold contains a pre-treated braided carbon fiber layer obtained in step S1. Under the conditions of temperature 150-200℃ and pressure 10-30 MPa, the thermally reversible covalent crosslinking agent in the plasticized melt penetrates and diffuses into the interior of the pre-treated braided carbon fiber layer and chemically bonds with the active functional groups on the surface of the carbon fiber to form a gradient interface layer. S4: Cooling and molding: After holding the pressure and cooling, open the mold and take out the product to obtain recycled PVC plastic.
7. The method for preparing recycled PVC plastic according to claim 6, characterized in that: The stretching rheological plasticizing extrusion equipment in step S2 is an eccentric rotor extruder or a blade extruder, with a stretching strain rate of 50 s⁻¹. -1 ~200s -1 .
8. The method for preparing recycled PVC plastic according to claim 6, characterized in that: The permeation and diffusion time in step S3 is 30-120 seconds, and the thickness of the gradient interface layer is 100-500 μm.